2021
DOI: 10.1186/s12909-021-02726-4
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative exploration of medical student experiences during the Covid-19 pandemic: implications for medical education

Abstract: Background During the Covid-19 pandemic medical students were offered paid roles as medical student healthcare assistants. Anecdotal reports suggested that students found this experience rich for learning. Previous studies have explored alternative models of student service, however this defined medical student support role is novel. Methods Individual semi-structured interviews were recorded with 20 medical students at a UK medical school explorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
1
15
0
3
Order By: Relevance
“…Within existing literature, we are aware of only two qualitative studies to explore medical student PIF during COVID. 12,25 A major focus of the first study was students' exploration of their roles in non-clinical environments; the second study explored student experiences on clinical placements as medical student healthcare assistants. Our study complements their findings by further exploring the larger theme of student-as-contributor when students were not able to participate clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Within existing literature, we are aware of only two qualitative studies to explore medical student PIF during COVID. 12,25 A major focus of the first study was students' exploration of their roles in non-clinical environments; the second study explored student experiences on clinical placements as medical student healthcare assistants. Our study complements their findings by further exploring the larger theme of student-as-contributor when students were not able to participate clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Near-peer-teaching and peer learning has become increasingly common during the pandemic to address this deficit [24]. Under pandemic conditions, hospitals can provide studens with new roles in patient care, adding to their learning opportunities [25]. Students could be offered modified in-person clinical rotations with pandemic precautions to complement the remote experiences we implemented [26].…”
Section: Discussionmentioning
confidence: 99%
“…For patient safety, experiential learning through clinical practice is important, but there seems to be a limit to this. Medical students felt that they had detracted from authentic communication with patients during clinical clerkship [ 13 ]. Senior medical students in the United Kingdom reported that the cancellation or postponement of objective structured clinical examination, assistantship, and electives due to COVID-19 affected their preparation for the first year of training [ 14 ].…”
Section: Discussionmentioning
confidence: 99%